Design and synthesis of gas-releasing antibiofilm polymers - Wang, Liping (Nanyang Technological University, 2020)
Infectious diseases are a leading cause of death worldwide. Many infections involve persistent biofilms on surfaces of indwelling medical devices or in host tissues and secretions. Microorganisms in biofilms are 10-1000 times less sensitive to antibiotics than their planktonic counterparts, and drug-resistant pathogens in biofilms are especially problematic. There is an urgent need to develop novel alternative antibiofilm materials to resist biofilm-associated infections. Bacterial colonization on blood-contacting catheters often results in biofilms that are recalcitrant to antibiotic treatment. A novel covalently linked nitric oxide (NO)-releasing coating was designed to resist catheter-related infections (CRIs) via a surface polyhydroxylation pre-treatment step. The polyurethane (PU) catheter surface was ozone pretreated and then polymerized to form a high surface density of poly(polyethylene glycol-hydroxyl terminated) brushes (i.e. P(PEG-OH)) which then underwent condensation with a mercapto-silane (i.e. MPS, mercaptopropyl trimethoxysilane) followed by S-nitrosylation to produce NO-releasing S-nitrosothiol (RSNO) on the substrate. The covalent immobilization of RSNO-donors prevents leaching and reduces the risks of cytotoxicity from leachable chemicals. Coated catheters displayed good biocompatibility and exhibited excellent antibiofilm formation activity in vitro (up to 99.99%) against a broad spectrum of Gram-positive and Gram-negative bacteria. Further, they showed good antibacterial colonization performance in vivo against Pseudomonas aeruginosa (P. aeruginosa) and methicillin-resistant Staphylococcus aureus (MRSA) in a murine subcutaneous implantation infection model. The surface chemistry to create high NO payload without NO-donor leaching can be translated to other medical devices. Recent studies indicate that carbon monoxide-releasing molecules (CORMs), a class of organometallic compounds, exert antibacterial activities through delivery of carbon monoxide (CO) molecules. A new-class CO-delivery system was developed by conjugating classical low molecular weight CORMs (i.e., [Ru(CO)3Cl2]2 and Mn(CO)5Br) onto a positively-charged carrier, polyimidazolium (PIM), giving cationic CO-releasing polymers Ru@PIM and Mn@PIM respectively. Compared with low molecular weight CORMs, polymeric CO vehicles showed good water solubility and reduced cytotoxicity to eukaryotic cells. After CO precursor conjugation to a cationic polymer scaffold, the duration of CO release was significantly extended to nearly 300 min, far exceeding the few minutes burst CO release from the corresponding low molecular CORMs. Ru@PIM and Mn@PIM were effective in inhibiting P. aeruginosa biofilm formation with inhibition ratios of more than 92% at 16 μg/mL and 99% at 32 μg/mL. Ru@PIM and Mn@PIM also demonstrated potent dispersal efficacy on well-established P. aeruginosa biofilms with log10 reduction at around 2.0-3.2 at the tested concentration range. These new CO-releasing polymers may have great potential as antibiofilm agents for biomedical applications.